Norma e contra-norma : um estudo estrutural de representação social sobre monogamia e não-monogamia - Mazzei, Vanessa Santa Rosa (2024)
Societies are permeated with norms and prescriptions that organize them and dictate what can or cannot be done. In the West, more specifically in Brazil, one of the hegemonic norms of social organization is the monogamous norm. Monogamy can be understood as a system of family organization where each person has exclusively one partner. Furthermore, monogamy shapes and delimits intimate and affective relationships, playing a crucial role in the formation and interconnection of social groups. It establishes guidelines for how, when, with whom, and in what way it is acceptable to feel, desire, and love. However, research has already demonstrated that monogamy is not natural even among mammals, showing that this is a socially constructed phenomenon. Currently, the question about monogamy has gained more social space and contributed to the formation of groups and practices that oppose monogamous ideals. The counter-norm phenomenon of non-monogamy constitutes a spectrum of relationship arrangements, ideals and practices that oppose, to some extent, the monogamous norm. With a view supported by the Theory of Social Representations from its structural approach, the present work intended to analyze the social representation of monogamy and non-monogamy for two distinct groups people who recognize themselves as monogamous and people who recognize themselves as non-monogamous and investigate the relationship that the norm and the counter-norm have between them, and between their groups. The research was divided into two complementary studies that used specific techniques from the Central Nucleus Theory. In the first exploratory study, data was collected from a free recall task of 5 words carried out online using GoogleForms with three inductive terms: (1) romantic relationship, 2) non-monogamous relationship, and 3) monogamous relationship), and participated in the collects 189 non-monogamous people and 124 monogamous people. Prototypical analyzes were carried out with the data using the IRAMUTEQ lexical analysis software. The second confirmatory study was carried out with 140 monogamous people and 140 non-monogamous people. The collection was carried out online using GoogleForms. Two centrality and structure confirmation techniques were used, Mise-en-cause and Choix-par-bloc. The results of the studies were analyzed together in the discussion. Such results indicated the non-existence of structured social representation regarding the monogamous relationship object for both monogamous and non-monogamous people. The non-monogamous relationship object presented a structure with confirmed centrality. We conclude that 1) monogamy, represented by the monogamous relationship object, can occupy another place in the hierarchy of the architecture of social thought, being at the ideological level, and not representational; 2) an ideology has the capacity to offer both incentives for its acceptance and internalization and reasons for its rejection and opposition; 3) a non-autonomous SR seems to be able to depend on an antagonistic main SR, and not necessarily on an SR to which it approaches. Furthermore, we highlight the importance of looking carefully at the characteristics of the phenomenon and the groups studied, in addition to the interpretation of the data